Implications of Digitalization on the Accounting Profession, Auditing Practices, and Accounting Education in Iraq: Challenges and Proposed Solutions - Hasan, Alia Ali (University of Thi-Qar Journal, 2025)
This research aims to investigate the impact of digital transformation on the accounting profession and accounting education by analyzing its implications for accountants’ performance efficiency and the ability of educational curricula to keep pace with technological advancements, as well as identifying the key challenges hindering the success of this process. The study examined the extent to which digital tools contribute to accelerating financial operations, facilitating auditing, and enhancing financial analysis capabilities, in addition to evaluating the effectiveness of curricula and academic staff in adapting to the digital environment. The findings revealed that digital transformation has created a qualitative shift in the accounting and auditing profession and contributed to improving the quality of accounting education. However, several obstacles still limit its effectiveness, most notably concerns related to information security, insufficiently qualified human resources, and limited financial resources. Accordingly, the research recommends developing accountants’ skills to adapt to digital requirements, updating measurement and disclosure systems and accounting standards in line with rapid technological developments, enhancing the competencies of faculty members in colleges of economics and business administration, updating financial and regulatory legislation, and strengthening accountants’ participation in workshops and specialized training programs to meet the demands of the digital economy.